Sixth Plan 1980-85 and Annual Plan 1981-82 Orissa (Draft) - Planning Commission (Planning Commission, 1980)
The compound growth rate of State income was 4'6 per cent in the Third Plan, 5-3 per cent: during the three Annual Plan, 2.6 per cent in the Fourth Plan and 2.5 per cent in the Fifth Plan. Growth rate achieved in the three Annual Plans was the highest followed by the growth achieved during the Third Plan. The growth rate of the economy from 1970-71 to 1978-79 was around 2.9 per cent.. Compared to earlier Plans, the growth rates during the Fourth and the Fifth Plans were very low, partly due to low levels of investment and partly due to severe inflation prevailing all over the country which brought down the real value of the investments. The per capita income of Orissa at 1970-71 prices was Rs. 395 in 1960-61. It rose to Rs. 501 in 1978-79, showing an increase of 27 per cent. The increase in the per capita income at 1970-71 prices was 10.1 per cent in the Third Plan, 9.6 per cent in the three Annual Plans, 0 8 per cent in the Fourth Plan, 1.4 percent in the Fifth Plan and 2.7 percent during the year 1978-79.
Annual Plan 1981-82 Orissa (Draft)
Government of Orissa